The Idea of Justice and A Just Society In Eastern Thought - Ozodboev Rakhimjon Rakhmonjon ogli (Indonesian Journal Publisher, 2026)
This article explores the concept of justice and the idea of a just society in Eastern thought, focusing on philosophical, ethical, and socio-political perspectives. It analyzes the views of prominent Eastern thinkers and highlights how justice is understood as harmony, balance, and moral responsibility within society. Special attention is given to the role of ethical norms, spiritual values, and governance principles in shaping a fair and stable social order. The study also examines the relevance of traditional Eastern ideas of justice in the context of modern societal development. The findings suggest that Eastern thought provides a holistic and value-oriented approach to justice, emphasizing collective well-being and moral integrity